Kondisi Sosial Ekonomi Nelayan Artisanal di Pantai Utara Provinsi Jawa Barat - Prihandoko S; Amri Jahi; Darwis S Gani; I.Gusti Putu Purnaba; Luky Adrianto; Iwan Tjitradjaja (Jurnal Penyuluhan, 2012)
This study is a research about the socio-economic conditions of artisanal fishermen in the northern coast ofWest Java Province. The purpose of this study was to provide data about the characteristics of socio-economicconditions of fishermen, especially in Java island in the middle is still very limited studies on these themes inIndonesia. Total sample of this study 400 respondents artisanal fishing households in the northern coast of WestJava Province who are scattered in the districts of Cirebon, Indramayu, Subang, Karawang and Bekasi withtechniques for sampling random clusters. The findings of this study again confirms the condition of marginal socialand economic needs of fishermen who co-management in the field of fisheries with the involvement of variousstakeholders. The findings of this study can also contribute in providing a description of one of the stakeholdersbenefiting from the resources of the coastal artisanal fishermen.Keywords: Socio-economic, fishermen, management.